HUBUNGAN ASUPAN NATRIUM, LEMAK, GANGGUAN MENTAL EMOSIONAL, DAN GAYA HIDUP DENGAN HIPERTENSI PADA DEWASA DI DKI JAKARTA - Ekaningrum, Annisa Yuri (Journal of Nutrition College, 2021)
Background: Non-communicable disease (NCD) that is still being serious problem in the worldwide and Indonesia is hypertension. DKI Jakarta was one of urban areas with prevalence of hypertension larger than prevalence in Indonesia, that was 34 %. High level of shift of life in urban areas affect unhealthy lifestyle such as eating pattern, physical activity, and mental and emotional health.Objective: This study aimed to analyze the relationship between sodium and fat intake, mental and emotional disorders, and lifestyle with hypertension in adult in DKI Jakarta.Methods: This study design was cross-sectional and used secondary data that was sourced from Indonesian Food Consumption Survey (SKMI) 2014 and Basic Health Research (Riskesdas) 2013. Subject in this study was respondents aged more than 18 years old who live in DKI Jakarta.Results: Bivariate analysis in this study showed that sodium intake (p=0.531) and fat intake (p=0.323) were not associated with hypertension. Emotional and mental disorders was associated with hypertension (p=0.001). Physical activity and sedentary behavior was not associated with hypertension (p=0.297; p=0.759). Food consumption behavior that was associated with hypertension was consuming salty foods more than once a day (p=0.039). Multivariate analysis results showed that respondents who suffer emotional and mental disorders tend to have a risk 4.095 times higher to suffer hypertension compared with people who not suffer emotional and mental disorders. Conclusion: Factor that is dominant affecting hypertension is mental and emotional disorders. Hypertension patients was suggested to manage stress that triggers to anxiety and depression.